Design of the SILELE Application Prototype Using the User-Centered Design (UCD) Approach - Agus Kurdiansyah (Institute of Information Technology and Social Science (IITSS), 2023)
The SILELE application was designed to assist catfish farmers in marketing their products and to serve as an information platform connecting farmers and buyers. The application was developed using the User-Centered Design (UCD) method to ensure that the interface aligns with user needs and expectations. This study applies the UCD approach to design an interactive prototype using Figma, a cloud-based collaborative design tool. Figma enables UI/UX designers to create and refine web and mobile application interfaces collaboratively in real time. The SILELE prototype demonstrates how a user-oriented design process can enhance system usability, functionality, and accessibility for both farmers and consumers engaged in the catfish trade.